(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
Studying the problem of women and the mechanisms of increasing their socio-political activity is one of the current issues of today. Because it is difficult to solve almost any problem of modern civil society, even the task of building a great country in the future, without the participation of women. We rely primarily on the young generation to build a great country in the future. Raising a child begins with proper family education. What kind of people our sons and daughters in the family grow up to be depends above all on our respectable women. Therefore, it is impossible to imagine life and development of society without women. They are the leading forces of the society, skillful and capable trainers, kind and intelligent educators.